Legal Counseling on Child-Friendly Elementary Schools as an Effort to Prevent Violence Against Children: Penguatan Implementasi Sekolah Ramah Anak melalui Penyuluhan Hukum di Sekolah Dasar - Nurzakiah, Nurzakiah; Ratri Novita Erdianti (Universitas Muhammadiyah Malang, 2026)
Violence against children in educational settings remains a significant issue that hinders the fulfillment of children’s rights to safe and dignified education. This community service activity aimed to strengthen the implementation of Child-Friendly Schools (CFS) through legal counseling at SDN 01 Temas Batu City. The activity involved 25 teachers and educational staff and was conducted through lectures and participatory discussions focusing on child protection principles and non-violent disciplinary practices. The impact of the activity was evaluated based on participants’ engagement, responses to case-based discussions, and feedback collected at the end of the session. The results indicate an improvement in participants’ understanding of the legal boundaries of disciplinary actions and increased awareness of child protection principles. Participants were able to distinguish between educational discipline and acts of violence. In addition, the school demonstrated initial commitment by planning to develop a formal CFS policy and establish an implementation team. This activity provides tangible benefits in the form of strengthened legal awareness, improved educator capacity, and an initial institutional foundation for implementing Child-Friendly Schools in a sustainable manner. Abstrak Kekerasan terhadap anak di lingkungan satuan pendidikan masih menjadi permasalahan serius yang menghambat pemenuhan hak anak atas pendidikan yang aman dan bermartabat. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk memperkuat implementasi Sekolah Ramah Anak (SRA) melalui penyuluhan hukum di SDN 01 Temas Kota Batu. Kegiatan ini melibatkan 25 guru dan tenaga kependidikan, serta dilaksanakan melalui metode ceramah dan diskusi partisipatif yang berfokus pada prinsip perlindungan anak dan praktik pendisiplinan non-kekerasan. Dampak kegiatan dievaluasi berdasarkan tingkat partisipasi peserta, respons terhadap diskusi berbasis kasus, serta umpan balik yang dikumpulkan pada akhir kegiatan. Hasil kegiatan menunjukkan adanya peningkatan pemahaman peserta mengenai batasan hukum dalam tindakan pendisiplinan serta meningkatnya kesadaran terhadap prinsip perlindungan anak. Peserta mampu membedakan antara pendisiplinan yang bersifat edukatif dan tindakan yang termasuk dalam kategori kekerasan. Selain itu, pihak sekolah menunjukkan komitmen awal dengan merencanakan penyusunan kebijakan formal SRA serta pembentukan tim pelaksana.Kegiatan ini memberikan manfaat nyata berupa peningkatan kesadaran hukum, penguatan kapasitas pendidik, serta menjadi fondasi awal dalam mewujudkan implementasi Sekolah Ramah Anak secara berkelanjutan.